Pengaruh Metode Vak Terhadap Pembelajaran Tolak Peluru Gaya Ortodok Pada Siswa - Hakim, Ahlu Annazar; Ardhika Falaahudin (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This research aims to determine the influence of the VAK (Visual, Auditory, Kinesthetic) learning method on the shot put learning outcomes in the orthodox style among 8th-grade students of SMP Negeri 1 Sedayu in the 2024/2025 academic year. The study was conducted using an experimental method involving two groups: the control class (VIII.A) with 32 students using a varied lecture method and the experimental class (VIII.C) with 32 students using the VAK method. The study measured learning outcomes in cognitive, affective, and psychomotor aspects obtained from the portfolio of the learning process for the orthodox style of shot put. The cognitive aspect was measured using a written test, the affective aspect with an observation rubric, and the psychomotor aspect through direct practical assessments of performing the orthodox shot put technique. The results showed that the average cognitive score for the control class was 66.88, while the experimental class had an average cognitive score of 95.00. The average affective score for the control class was 75.52, whereas the experimental class had an average affective score of 97.22. The average psychomotor score for the control class was 64.26, while the experimental class had an average psychomotor score of 92.77. Thus, the VAK method significantly impacted the improvement of students' learning outcomes. The success rate reached 83.93%, with students in the experimental class achieving